Решите пожалуйста:(а-3)^2= (х+3)^2= (х+у)^2= (х-у)^2= (2х-3)^2= (2у-4)^2=...

0 голосов
54 просмотров

Решите пожалуйста:(а-3)^2=
(х+3)^2=
(х+у)^2=
(х-у)^2=
(2х-3)^2=
(2у-4)^2=
(3-х)(9+3х+х^2)=
(6+х)(36-6х+х^3)=


Алгебра (12 баллов) | 54 просмотров
Дано ответов: 2
0 голосов

(a – 3)² = a² - 6a + 9

(x + 3)² = x² + 6x +9

(x + y)² = x² + 2xy + y²

(x – y)² = x² - 2xy + y²

(2x – 3)² = 4x² - 12x +9

(2y – 4)² = 4y² - 16y + 16

(3 – x)(9 + 3x + x²) = 27 - x³

(6 + x)(36 – 6x + x³) = x⁴ + 6x³ - 6x² + 216

(216 баллов)
0 голосов

1 x^{2} +6x +9  1a^2-6a+92  x^{2} +2xy+y^2
3 x^2-2xy+y^2
4 4x^2-12x+9
5 4y^2 -16y+16
6 27-x^3
7 6^3+x^3

(64 баллов)